2002
DOI: 10.1038/sj.bjc.6600234
|View full text |Cite
|
Sign up to set email alerts
|

Aminolaevulinic acid-induced photodynamic therapy: cellular responses to glucose starvation

Abstract: Photodynamic therapy is a cancer treatment based on the interaction of light, oxygen and a photosensitiser. Protoporphyrin. IX is an endogenous photosensitiser derived from the pro-drug aminolaevulinic acid. Tumours contain areas of hypoxia and hypoglycaemia. Tumour cells adapt to these conditions by stress protein induction which may induce resistance to cancer therapies. The effect of chronic hypoglycaemia on sensitivity to aminolaevulinic acid-induced photodynamic therapy in vitro was studied in MCF-7, huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…Recent studies have indicated that nutrient deprivation, particularly glucose, may play a major role in tumor cell tolerance to a generally oxidative stress environment in solid tumors (23, 24). It has been demonstrated that chronic exposure to low glucose have caused photo dynamic therapy (PDT) resistance in breast cancer cells (25). Glucose regulated protein GRP78 is believed to play a major role in the survival of cancer cells during hypoxia, low pH and stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that nutrient deprivation, particularly glucose, may play a major role in tumor cell tolerance to a generally oxidative stress environment in solid tumors (23, 24). It has been demonstrated that chronic exposure to low glucose have caused photo dynamic therapy (PDT) resistance in breast cancer cells (25). Glucose regulated protein GRP78 is believed to play a major role in the survival of cancer cells during hypoxia, low pH and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of prolonged low glucose exposure in PDT resistance has been demonstrated in breast cancer cells (25), the impact of short-term low glucose exposure has not been studied for any kind of cancer therapy. It is important to determine the impact of short-term exposure to low glucose prior to therapy since it is likely that short term exposure to low glucose and low oxygen may also occur in solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the effect of chronic hypoglycemia on sensitivity to aminolaevulinic acid-induced PDT in vitro was studied in human breast cancer cells. It was shown that photodynamic therapy sensitivity was reduced in glucose-deprived cells [47] (Figure 1). Additionally, tumors, due to their abnormal vasculature, are characterized by a more acidic environment compared to their surrounding normal tissues.…”
Section: Estradiol Receptor Tetraphenylporphyrinmentioning
confidence: 99%
“…As a result, it is possible to find a concentration gradient of the drug within the breast TME between the tumor tissue and the normal surrounding tissue. By injecting glucose, it is possible to further selectively reduce the extracellular pH value of tumors [49] , and to make tumor cells more sensitive to PDT treatment [47] . This will, in 905 December 10, 2014|Volume 5|Issue 5| WJCO|www.wjgnet.com PDT is one of the alternative methods for breast cancer treatment and involves: (1) administration of a photosensitizer (PS), which is internalized into either tumor cells or surrounding vasculature; (2) local irradiation at a wavelength corresponding to the absorbance peak of the PS; and (3) light activation of the PS, which promotes cell death mainly by apoptosis.…”
Section: Estradiol Receptor Tetraphenylporphyrinmentioning
confidence: 99%
“…The cells are of human origin and presumed to conserve some differentiated mammary epithelial cell function (22), that is, potentially the PEPT2 transporter. MCF-7 cells have previously been used in studies with photosensitizers (23). In particular, the effect which different oil/water (o/w) emulsions have on the amount of PpIX formed was evaluated.…”
Section: Introductionmentioning
confidence: 99%